A Pilot Study Investigating the Effect of Serum 25-Hydroxyvitamin D on Device-Estimated Sleep Metrics in Young Black Women: A Single-Arm Open-Label Clinical Trial - Michele N D’Agata; Krista M Szymanski; Freda Patterson; Mackenzie L Rattigan; Alexs A Matias; David G Edwards; Christopher R Martens; Sushant M Ranadive; Melissa A Witman (SLEEP Advances, 2026)
Abstract Study Objectives Vitamin D deficiency has been linked to poor sleep health outcomes in the general population. Black women (BLW) experience a higher prevalence of vitamin D deficiency and short and disturbed sleep compared with other races. Therefore, this study tested cross-sectional associations between serum 25-hydroxyvitamin D concentration ([25(OH)D]) and sleep health estimates in young adult BLW, followed by an 8-week vitamin D supplementation intervention. Methods Forty-three 18-30-year-old BLW underwent blood sampling for serum [25(OH)D]. Sleep metrics were derived from 14-days of wrist accelerometry. Thereafter, participants with [25(OH)D] <30 ng/ml (N=16) completed an 8-week vitamin D3 supplementation intervention (5,000 IU/day) and repeated blood sampling and sleep monitoring. Results Linear regressions demonstrate significant cross-sectional associations for [25(OH)D] with sleep efficiency (β=0.11, P=0.03; %) and sleep onset standard deviation (SOSD) (β=-0.53, P=0.04; minutes), but no associations with sleep duration or sleep duration standard deviation (SDSD) (P>0.18). Among intervention participants, paired-sample t-tests demonstrate a significant increase in [25(OH)D] (16.8±7.0 vs. 55.3±10.0, ng/ml; P<0.001), however, no changes were observed among actigraphy-derived sleep variables (all P>0.21). Conclusions [25(OH)D] was cross-sectionally associated with sleep efficiency and SOSD, however, intervention results from this pilot study do not demonstrate a beneficial effect of vitamin D on several device-estimated sleep metrics in young BLW.